Frequency response of the leap motion controller and its suitability for measuring tremor. (January 2019) - Kincaid, Clay J.; Vaterlaus, Austin C.; Stanford, Nathan R.; Charles, Steven K.
Highlights: The frequency response of the Leap Motion Controller (LMC) was characterized. The bandwidth of the LMC and its suitability for measuring tremor were determined. An inverse filter was created to measure tremor more accurately. Abstract: Although tremor is one of the most common movement disorders, it is evaluated using relatively coarse clinical scales. We propose to measure tremor in clinical settings using the Leap Motion Controller (LMC), which is a markerless motion capture sensor that has a low cost, zero set-up time, and dynamic accuracy of 1.2 mm. However, the frequency response of the LMC has not been characterized, so its ability to track oscillations such as tremor is unknown. To characterize the frequency response of the LMC, we measured the position of a mannequin hand simultaneously with the LMC and a high-resolution encoder while the mannequin hand oscillated at various combinations of frequency (1–15 Hz) and amplitudes (0.01–30 mm). We calculated the magnitude ratio and phase shift of the LMC and found the bandwidth of the LMC to range from 0–3 Hz to 0–5 Hz for tremor amplitudes greater than the dynamic accuracy. This bandwidth is too small to accurately measure most tremors. However, we developed an inverse filter to estimate the actual tremor amplitude and phase despite the limited bandwidth. Over the combinations of frequency and amplitude mentioned above, the inverse filter estimated the actual tremor amplitude and phase with errors of 3% and 2%, respectively.